The Content Governance Dilemma Digital Constitutionalism, Social Media and the Search for a Global Standard - Palladino, Nicola (Springer / Palgrave McMillan, 2023)
One of the main issues of global social media governance relates to the definition of the rules governing online content moderation worldwide. One could think that it would be sufficient for online platforms to refer to existing international human rights standards. However, a more careful analysis shows that international law provides exclusively general principles and that a single human rights standard does not exist. Since their inception, major social media platforms have set their own rules; yet this normative autonomy too has raised serious concerns. The current situation exposes a dilemma for online content governance that seriously affects the operations of social media companies and impacts on the exercise of fundamental rights by users as well as digital policy strategies.
PUBLISHED
Keywords: Digital constitutionalism; Constitutionalisation; International law; Private norms; Normative dilemma; Online content governance; Social media